Investigation of miscellaneous hERG inhibition in large diverse compound collection using automated patch-clamp assay - YU Hai-bo; ZOU Bei-yan; WANG Xiao-liang; LI Min (Acta Pharmacologica Sinica; Vol 37, No 1 (January 2016): Acta Pharmacologica Sinica(Special Feature:Ion Channels）, 2017)
Aim: hERG potassium channels display miscellaneous interactions with diverse chemical scaffolds. In this study we assessed the hERG inhibition in a large compound library of diverse chemical entities and provided data for better understanding of the mechanisms underlying promiscuity of hERG inhibition. Methods: Approximately 300 000 compounds contained in Molecular Library Small Molecular Repository (MLSMR) library were tested. Compound profiling was conducted on hERG-CHO cells using the automated patch-clamp platform–IonWorks QuattroTM. Results: The compound library was tested at 1 and 10 μmol/L. IC50 values were predicted using a modified 4-parameter logistic model. Inhibitor hits were binned into three groups based on their potency: high (IC50